2021
DOI: 10.3390/nano11082025
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Inkjet-Printed Reduced and Functionalized Water-Dispersible Graphene Oxide and Graphene on Polymer Substrate—Application to Printed Temperature Sensors

Abstract: The present work reports on the detailed electro-thermal evaluation of a highly water dispersible, functionalized reduced graphene oxide (f-rGO) using inkjet printing technology. Aiming in the development of printed electronic devices, a flexible polyimide substrate was used for the structures’ formation. A direct comparison between the f-rGO ink dispersion and a commercial graphene inkjet ink is also presented. Extensive droplet formation analysis was performed in order to evaluate the repeatable and reliable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…Flexible printed electronics (FPEs) are expected to dominate soon in the field of electronics because they have shown great potential in a wide range of applications [1] including sensors and microheaters [2,3], transistors [4], light-emitting diodes (LEDs) and organic LEDs (OLEDs) [5,6], solar cells [7], and wearable electronics and e-textiles [8,9]. FPE development requires the connection of flexible conductive structures, interfaces, and contacts, which can be created through the printing of conductive, semiconductive, and dielectric nanomaterials on suitable substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Flexible printed electronics (FPEs) are expected to dominate soon in the field of electronics because they have shown great potential in a wide range of applications [1] including sensors and microheaters [2,3], transistors [4], light-emitting diodes (LEDs) and organic LEDs (OLEDs) [5,6], solar cells [7], and wearable electronics and e-textiles [8,9]. FPE development requires the connection of flexible conductive structures, interfaces, and contacts, which can be created through the printing of conductive, semiconductive, and dielectric nanomaterials on suitable substrates.…”
Section: Introductionmentioning
confidence: 99%
“…It is prepared via a reliable, affordable, facile, one-pot method that allows the simultaneous reduction and functionalization of GO using sulfonated aromatic diamines. Furthermore, our previous studies have shown that due to these properties, it is a promising material in the field of printed electronics [ 38 , 39 , 40 ], for example, as a pigment in conductive water-based inks for gravure and flexography or as an ink for inkjet-printed temperature sensors. In this work, a water dispersion of this highly hydrophilic material was used without any surfactant or additive.…”
Section: Resultsmentioning
confidence: 99%
“…An aqueous graphene oxide (GO) dispersion (1 mg/mL) was prepared following a previously described method [ 38 , 39 ]. Then, an appropriate amount of 2,4-diaminobenzenesulfonic acid (2,4-DBSA) was added in the GO dispersion using a mass ratio GO:2,4-DBSA equal to 1:3.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations